A Pilot Study on Intravesical Administration of Curcumin for Cystitis Glandularis. (22nd May 2013) - Lu, Qiong; Jiang, Fen; Xu, Ran; Zhao, Xiao-Kun; Zhong, Zhao-Hui; Zhang, Lei; Jiang, Hong-Yi; Yi, Lu; Hou, Yi; Zhu, Xuan
Abstract : Cystitis glandularis (CG) is a proliferative disorder in the urinary bladder. The outcome of current treatments in some patients is not satisfactory. Curcumin, a herbal medicine that has been used for centuries, has shown great potential in treating various diseases. Our pilot study aimed to explore the feasibility of an intravesical treatment for CG using curcumin. 14 patients diagnosed with CG that remained symptomatic after primary treatments were enrolled, underwent a 3-month curcumin intravesical treatment (50 mg/50 mL, 1 hour, once per week for first 4 weeks and once per month for next 2 months) and were followed up for 3 months. Efficacy of the treatment was evaluated using core lower urinary tract symptom score (CLSS) questionnaire. 10 patients demonstrated persistent improvement in symptoms up to the end of the 6-month study. Their CLSS decreased significantly after the 3-month treatment (6.0 ± 0.8 ; P < 0.01 ) from the baseline (10.5 ± 1.6 ) and maintained decreasing till the end of the study (6.2 ± 0.7 ; P < 0.01 ). 4 patients were classified as nonresponders. Our study suggests the feasibility of further randomized controlled trials on curcumin intravesical treatment in CG patients who remain symptomatic after primary treatments.